Sistemas de Informações Geográficas (SIG) aplicado a Gestão de Recursos Naturais: Atlas do aproveitamento de água da chuva nas ilhas de Belém-PA - Iniciativas, Demandas e Potencialidades - MACEDO, Robson Raposo (Universidade Federal do Pará, 2018)
Garret Hardin's (1968) understanding of the "tragedy of the commons" points to the need to effect the act or effect of managing the available natural resources, enabling the projection of a more sustainable future for present and future generations. In this sense, this work presents a brief characterization of local initiatives for the use of rainwater in the islands of the city of Belém do Pará, provides the systematization of data and information considering various aspects related to water use, stating that it is impossible to construct practices Addressing environmental issues in isolation. Therefore, the present research brings as an dissertation an ATLAS of the initiatives of use of rainwater in the estuary of Belém, considering issues related to the use of water in the various forms of appropriation of this natural resource essential to the promotion of local development. The ATLAS is constituted of a diagnosis presented by means of thematic maps, bringing the discussion questions related to "Spatial distribution of initiatives of use of rainwater; Systematization of data using the Geographic Information System (GIS); Information management and environmental quality; Management of natural resources and social technologies ". The study considered as an object of analysis, initiatives for the use of rainwater in the context of 9 (nine) islands of Belém. It locates and describes 4 different models of rainwater harvesting, among a population of approximately 3,046 Inhabitants, of which 90% do not have access to basic public services such as water supply through the general network, domestic waste collection and sewage systems via the general network. It also presents models of rainwater use integrated with the use of river water and wells located in regions close to the islands, showing an important example of systemic management of water resources, actions aligned, consciously or not, with the National Water Resources Policy. It concludes that the initiatives identified are in line with the objectives and guidelines proposed in the Municipal Master Plan of Belém and presents a thematic diagnosis that reveals a situation of social and environmental risk due to the lack of basic sanitation services to the local community. As a contribution, in addition to providing the Atlas in sigweb format, this research proposes the use of the Atlas as a tool to assist environmental management instruments, demonstrating how the use of GIS through the Atlas can contribute to the management of natural resources considering the various themes Which involve the use of social technologies in the search for sustainability in water consumption in the city of Belém do Pará.